Advances in monitoring transboundary water cooperation? Reflecting on the development and implementation of SDG indicator 6.5.2. Issue 3 (3rd April 2022) - Rieu-Clarke, Alistair S.; Bernardini, Francesca; Tiefenauer-Linardon, Sarah; Aureli, Alice
ABSTRACT: The Sustainable Development Goals (SDGs) indicator framework marks the first time that a specific indicator on transboundary water cooperation (indicator 6.5.2) has been adopted within an inter-governmental process. Achieving the political and technical support for this was not easy. However, through widespread consultation, and by building upon existing practice relating to water cooperation, the indicator was ultimately approved. The 2017 and 2020 reporting exercises demonstrated the robustness and value of the indicator. Having operational arrangements in place is critical to ensuring that transboundary waters are managed in an equitable and sustainable manner. SDG indicator 6.5.2 offers great potential in supporting that effort.